Understanding Cyclic Fatigue in Three Nickel–Titanium Pediatric Files: An In Vitro Study for Enhanced Patient Care - Alwaleed Abushanan; Rajashekhara Bhari Sharanesha; Fahd Aljarbou; Hadi Alamri; Mohammed Hamad Almasud; Abdulfatah AlAzmah; Sara Alghamdi; Mubashir Baig Mirza (Medicina)
Background and Objectives: Nickel–titanium (Niti) instruments have enhanced root canal cleaning in primary teeth, but file fractures are still common. Materials and Methods: This study evaluated the cyclic fatigue resistance of 120 Niti files from four different systems, A: Kedo SG (n = 30); B: Neoendo Pedoflex (n = 30); C: Pedoflex Waldent files (n = 30); and D: Vortex Blue files (n = 30). All the files had similar tip diameters (0.25 mm) and tapers (0.4%) and underwent heat treatment during manufacturing. Cyclic fatigue tests showed notable variations in cycles to fracture (NCF) across groups. All fracture surfaces of the files were assessed through scanning electron microscopy. Results: The mean values achieved in the experimental groups (A, B, C) were less than those in the control Group D (976.90 ± 1085.19). Files in Group A demonstrated the highest NCF (697.01 ± 420.09), while Pedoflex files in Group C showed the lowest values (203.88 ± 155.46). Statistical analysis using the Mann–Whitney test revealed significant differences between Group C and Groups A, B, and D and no differences among Groups A, B, and D. Conclusions: These findings suggest that Kedo SG and Neoendo Pedoflex files offer comparable cyclic fatigue resistance to Vortex Blue files. In contrast, Pedoflex Waldent files exhibit lower resistance to fracture.